Judges and the making of international criminal law - Powderly, Joseph (Leiden studies on the frontiers of international law ;, 2020)
"In 'Judges and the Making of International Criminal Law' Joseph Powderly explores the role of judicial creativity in the progressive development of international criminal law. This wide-ranging work unpacks the nature and the contours of the international judicial criminal function. Employing empirical, theoretical, and doctrinal methodologies, it interrogates the profile of the international criminal bench, judicial ethics, and the interpretative techniques that judges have utilized in their efforts to progressively develop international criminal law. Drawing from the work of Hersch Lauterpacht, it proposes a conception of the international criminal judicial function that places judicial creativity at its very heart. In doing so it argues that international criminal judges have a central role to play in ensuring that modern international criminal law continues to adapt to a volatile global environment, where accountability for crimes that shock the conscience of humanity is as much needed as at any moment in recent history"--